Physiological and biochemical responses to acute ozone-induced oxidative stress in Medicago truncatula - Puckette, Michael C (Plant physiology and biochemistry : PPB, 2007)
Oxidative signaling mediated by reactive oxygen species (ROS) is a central component of biotic and abiotic stresses in plants. Acute ozone (O(3)) fumigation is a useful non-invasive treatment for eliciting endogenous ROS in planta. In this study, 38 different accessions of the model legume, Medicago truncatula, from various geographical regions were fumigated with 300 nmol mol(-1) of O(3) for a period of six hours. Phenotypic symptoms were evaluated 24 and 48 h after the end of treatment. A majority of the accessions showed distinct visible damage. Eight accessions showing varying sensitivities to ozone were subjected to biochemical analysis to evaluate correlations between ozone damage and levels of ROS, antioxidants, and lipid peroxidation. Two-way analysis of variance indicated highly significant interactions between O(3) damage and levels of ROS, ascorbate, glutathione and lipid peroxidation. There were significant differences among the accessions for these traits before and after the end of O(3) fumigation, as indicated by equal variance Student's t-test. This study suggests that multiple physiological and biochemical mechanisms may govern O(3) tolerance or sensitivity. Surveying a large collection of germplasm led to identification of multiple resistant and sensitive lines for investigating molecular basis of O(3) phytotoxicity. The most resistant JE154 accession also showed enhanced tolerance to chronic O(3) and dehydration stress, suggesting germplasm with increased tolerance to acute O(3) can be a useful resource for improving resistance to multiple abiotic stressors